1999
DOI: 10.1046/j.1365-2281.1999.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled oral glucose tolerance test: evaluation of insulin resistance with an insulin infusion algorithm that forces the OGTT glycaemic curve within the normal range. A feasibility study

Abstract: This is a technical study to show the feasibility of a computer-controlled oral glucose tolerance test (OGTT) using a specific algorithm, consisting of an OGTT carried out while insulin is infused as required to keep glycaemia within the normal range (National Diabetes Data Group 1979 criteria). This technique allows (a) the amount of insulin (insulin area) required to maintain a normal glycaemic curve to be assessed, a parameter indicating the degree of insulin resistance; and (b) the unique parameter consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Therefore, the primary aim of the work described here was to determine whether the glucose responses from either an OGTT or a MTT could be used as drivers of the Boston Complete NEFA model or the Boston Minimal NEFA model. The OGTT and MTT typically involve far fewer samples than the IVGTT, and sampling tends to be much more dispersed, with intersample intervals in some protocols being in excess of 30 min (30,38). Thus, in this investigation, the outcome is influenced not just by the difference in the manner of administering the glucose challenge, but also by differences in the number of plasma samples and the intersample intervals employed in each protocol.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the primary aim of the work described here was to determine whether the glucose responses from either an OGTT or a MTT could be used as drivers of the Boston Complete NEFA model or the Boston Minimal NEFA model. The OGTT and MTT typically involve far fewer samples than the IVGTT, and sampling tends to be much more dispersed, with intersample intervals in some protocols being in excess of 30 min (30,38). Thus, in this investigation, the outcome is influenced not just by the difference in the manner of administering the glucose challenge, but also by differences in the number of plasma samples and the intersample intervals employed in each protocol.…”
mentioning
confidence: 95%
“…The glucose data shown in the originalFig. 2, A and Bfrom Volpicelli et al(38) and the NEFA data shown in originalFig. 5, A and B(38) were used in this modeling.…”
mentioning
confidence: 99%